The Challenges Teachers and Students Face in Implementing the Merdeka Belajar Curriculum for Teaching and Studying English at SMP Negeri 5 Sangatta Utara - Dwi Fachriani Astuti; Udi Samanhudi; Widya Rizky Pratiwi (LP. Ma'arif Janggan Magetan, 2024)
This study investigates the implementation of the Merdeka Belajar Curriculum in teaching English at SMP Negeri 5 Sangatta Utara during the academic year 2023-2024. The research aims to identify teachers' and students' challenges to teach and study English. Using a qualitative descriptive research design, data were collected through participant observation, semi-structured interviews, and documentation review. The findings reveal that the school adopted the Independent Changing option of the Merdeka Belajar Curriculum, utilizing a Genre-Based Approach (GBA) in English lessons. However, challenges such as the lack of differentiated instruction, inadequate technological resources, and poor classroom infrastructure were identified. The study highlights the need for specialized teacher training, improved communication with parents, and enhanced support systems to overcome these challenges. The research contributes to understanding the practical aspects of curriculum implementation in remote areas, providing insights into effective strategies to enhance English language learning outcomes.